EVALUASI KINERJA KEUANGAN KOPERASI DARI ASPEK EFEKTIVITAS BERDASARKAN PEDOMAN PEMERINTAH STUDI KASUS KSU PERWIRA PURBALINGGA - Aprilia, Dwiani Nursasi; Arruum, Cintia; Nuristiyanti, Nia; Wiratno, Adi (Jurnal Riset Akuntansi Soedirman, 2023)
This study aims to determine the Financial Performance of PERWIRA Purbalingga's Multi-Business Cooperative (KSU) from a productivity aspect according to Government guidelines in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/M.KUKM/V/2006. Data collection was carried out through interviews with cooperative management. collect data such as balance sheets, income statements, the history of the establishment of the cooperative, organizational structure, and the articles of association and bylaws of the cooperative. in terms of the development of profitability, Return on Assets, Asset Turn Over (ATO), Net Profit Margin, and total debt to own capital at KSU "PERWIRA" from 2016 to 2022 KSU Perwira is in the very good category. In contrast to the evaluation results on total liabilities to assets which show unfavorable developments.